Sofrimento e resiliência: o impacto do abuso sexual na saúde de jovens mulheres vitimadas em Manaus - Martins, Rosimeire de Carvalho (2007)
This research investigated the impact of the sexual abuse in the health of victimized women in the city of Manaus, as well as the social representations of the abuse, aggressor and mother. There were interviewed eighteen sexually victimized women; twelve of them were victimized by an unknown person and six by someone from her own family group. In the first part of the interview protocol we collected social demographic informations of the participants and in the second part we asked them to talk freely about what happened. The data of the interviews was analysed by the technique of theme analysis of contempt. We verified that in 50% of the women the negative effects in their health remained, even after one year after the violence, making their sexual, social and family relations difficult. In these cases we observed they could not count on the support of the family, mother or professionals. In the other 50%, we identified a growing movement to overcome the stress and to retrieve their lives, and that the social and family support, as well as the psychological support service act as helpers in the individual process of facing the effects of the suffered violence. Women represent the sexual abuse as an act of extreme violence, emphasysing mainly the physical strength and the violence of the abuser. We identify an ambiguity in the group of women that suffered abuse inside their families, because part of the women did not perceive the atc as violent. The social representations about the abuser refer to a man that posess authority, power and strength, always older, violent and does not worry about the will of the victimized women, we also verify ambiguity in the representations of the group of women that sufferen sexual violence inside the family, because the abuser was perceived as someone friendly. The mother is represented by a major part of the interviewed women as a “bad mother”, characterized as insensitive, negligent and that lack comffort, with whom they have a conflictuous relatioship. The “good mother” was reffered by a few interviewed women indicating that the relationship among them was less conflictuous. We conclude that the genuine pain exteriorized in the speeches of the victimized women, through the explanation of a diversity of physical and psychological effects and by representations composed by negative elements mainly, show a shameful social reality and also tolerant with the sexual violences performed against women, adolescents and children. Although we have identified that a part of the women is resilient and tries to overcome the evil effects of the occurrence, we understand that a lot has to be done to help assistance and preventive measures can be adopted observing the writs of the Brazilian citizens, knowing the effects of this type of violence can cause.